Ewolucja rynku wewnętrznego w Polsce - Kramer, Teodor (Wydział Prawa i Administracji UAM, 1967)
In planned economy the market is a mechanism of outlet in the short run. It does not determine directly either the production or prices. The market is constituted by the functioning of state's mechanisms. In such state of affairs there remains the problem how wide ought to be the field of choice for individual consumer and how much influence can he exert on the construction of current and perspective trade planning. For the socialist society there exist a free choice of consumption. This is leading, however, to such a quantity of various alternatives of meeting one's needs, that it can be solved only by market apparatus. The acceptance of the principle of free choice of consumption may have manifold repercussions of the planned economy, depending on the home market's model. We can distinguish two market models in the sphere of servicing individual consumption. The first one is characteristic to the initial phases of industrialization. That model of the market — is called a restraint market. The consumer conserves here is free choice of consumption, but his choice acts exert only an influence on the division of offered consumption goods. The negative effects of a restraint market get accumulated and become with a time a market disturbing factor. With the undertaken reforms, we can distinguish nowadays a model of a developed market, characteristic for the higher phases of economic growth. The specific trait of that market model is the fact, that the acte of choice individual consumers constitute the starting points for production decisions. With the assumption of rigid prices, the market equilibrium can be safeguar-ded only by means of planning. Of paramount importance here is the supply elasticity, which can be assured by reserves, foreseen in various balances, and especially in the production sphere.
The evolution of inner market in planned economy